Articulating care and responsibility in design : A study on the reasoning processes guiding health innovators' 'care-making' practices - Rivard, Lysanne; Lehoux, Pascale; Hagemeister, Nicola (Design Studies, 2021)
This article explores how health innovation designers articulate are and responsibility when designing new health technologies. Towards this end, we draw on Tronto’s ethic of care framework and Responsible Research and Innovation (RRI) scholarship to analyse interviews with Canadian health innovators (n ¼ 31). Our findings clarify how respondents: 1) direct their attention to needs and ways to improve care; 2) mobilise their skill set to take care of problems; 3) engage in what we call ‘care-making’ practices by prioritising key material qualities; and 4) operationalise responsiveness to caregivers and care-receivers through user-centred design. We discuss the inclusion of health innovation designers within the care relationship as ‘caremakers’ as well as the tensions underlying their ways of caring and their conflicting responsibilities.
Keywords: Canada; Publication UdeM; Responsible research and innovation; Réservé UdeM; Éthique